Automation trust and attention allocation in multitasking workspace. (July 2018) - Karpinsky, Nicole D.; Chancey, Eric T.; Palmer, Dakota B.; Yamani, Yusuke
Abstract: Previous research suggests that operators with high workload can distrust and then poorly monitor automation, which has been generally inferred from automation dependence behaviors. To test automation monitoring more directly, the current study measured operators' visual attention allocation, workload, and trust toward imperfect automation in a dynamic multitasking environment. Participants concurrently performed a manual tracking task with two levels of difficulty and a system monitoring task assisted by an unreliable signaling system. Eye movement data indicate that operators allocate less visual attention to monitor automation when the tracking task is more difficult. Participants reported reduced levels of trust toward the signaling system when the tracking task demanded more focused visual attention. Analyses revealed that trust mediated the relationship between the load of the tracking task and attention allocation in Experiment 1, an effect that was not replicated in Experiment 2. Results imply a complex process underlying task load, visual attention allocation, and automation trust during multitasking. Automation designers should consider operators' task load in multitasking workspaces to avoid reduced automation monitoring and distrust toward imperfect signaling systems. Highlights: We examined relationships among visual attention, workload, and trust in automation. Operators attended to automation less when the primary task is more difficult. Trust in automation declined when the primary task demanded more attention. Task load in multitasking workspace impacts monitoring of and trust in automation.